Modern legal language: universality and aloofness - Samokhvalova, A. V.; Самохвалова, А. В.; Robu, N. V.; Робу, Н. В. (Одеса : Фенікс, 2014)
Mentioned above allows to consider modern legal language to include abstraction, impersonality and objectivisation, neutrality and even metaphors in it in order to be clearly understood by lawyers and simple citizens.
Robu N. V., Samokhvalova, A. V. Modern legal language: universality and aloofness / N. V. Robu, A. V. Samokhvalova // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 613-614.
Keywords: Modern legal language; современный юридический язык; сучасна юридична мова